Effect of Node Position and Number of Stem Cutting on The Growth and Yield of ‘katuk’ (Sauropus androgynus (L.) Merr.) - Solikin, Solikin (El-Hayah : Jurnal Biologi, 2018)
Katuk (Sauropus  androgynus (L.) Merr.) has potential as a vagetable and medicinal plant.  This study aimed  to determine effect of node  position and number of stem cuttings  on the  growth  of  katuk. The experiment   used  Completely Randomized Design with two treatments arranged in split  plots. The node  position of stem cuttings as the main plot consists of top stem cutting (T, top – 8 nodes under shoot tip),  middle stem cutting (M, 8 – 11 nodes under shoot tip) and bottom stem cutting (B, 16-20 nodes under shoot tip). The node number of stem cuttings as a subplot consists of 2 nodes  (J1), 3 nodes (J2), 4 nodes (J3), and 5 nodes (J4). Each treatment  combination was replicated  three times.The results revealed that the top stem cutting  resulted in the  highest  root, total plant dry weight and leaf area, as well stem cutting with 4 nodes produced  the highest total plant dry weight and leaf area.